Toxicological study of aqueous and ethanolic extracts from Pueraria mirifica Airy Shaw & suvatabandhu on male rats - P. Sanchanta (2018)
This research was carried out to investigate toxic effects of aqueous and ethanolic extracts from Pueraria mirifica Airy Shaw and Suvatabundhu on male rats. Both extracts at the doses of 400, 600 and 800 mg/kg bw were orally given to male rats for 4 weeks. The kidney and liver functions, histopathological and hematological alterations, including micronucleus formation were evaluated. The effect on rat body weight was also observed. The results showed that both extracts of all doses used had no effects on the kidney and liver functions according to the normal values of blood urea nitrogen (BUN), creatinine (Crea), aspatate aminotransferase (AST) and alanine aminotransferase (ALT). However, histological alteration of both organs were observed in some rats treated with both extracts. Hematologically, total white blood cell count was not different from that of controls and differential cell count was normal, although lymphocytes and neutrophils in some treated rats was slightly different from those of control group. However, rats in all treated groups showed significantly lower packed red cell volume (PCV) than controls (p < 0.01) and their micronuclei in polychromatic erythrocytes (PCE) were significantly higher than those of controls (p < 0.05). These results revealed that both aqueous and ethanolic extracts of P. mirifica affected the red blood cell formation and also acted as a mutagenic agent. Furthermore, all treated rats had significantly lower body weight gain as compared to control (p < 0.01). It could be clearly concluded that the extracts from P. mirifica at the doses used in this study tend to be toxic to rats. Nevertheless, its mutagenic effect is not in the same level as cyclophosphamide, a genuine mutagen. © ISHS 2005.